Possibilities for long-term shifts in higher education assessment praxis: Reflecting on COVID-19 as a stimulus for change - Dison, L.; Padayachee, K. (South African Journal of Higher Education, 2022)
It is widely recognized that assessment impacts on the process and behavior of learning. In this article, we, as academic staff development professionals in two faculties at a research intensive South African university, explore the assessment challenges, processes and behaviours that emerged in the context of Emergency Remote Teaching and Learning during the Covid 19 pandemic. We argue that an analysis of changes in assessment culture and behaviour point to possibilities for a shift from the pre-Covid-19 dominance of the “assessment of learning” paradigm, to an orientation of assessment where both “assessment of learning” and “assessment for learning” are more equitably balanced, with potentially profound implications for shaping the ways students construct their understandings and succeed academically.